The role of comprehensive schools in supporting the well-being of Northern-Finnish young people as perceived by the young people, parents and carers - Lauri Lantela; Suvi Lakkala (University of Aberdeen, School of Education, 2020)
In Finland, services aimed at supporting the well-being of young people and their families are fragmented. This research explores the expectations of young people and parents and carers concerning the well-being of young people and their perceptions of the school's role in supporting young people. The research was conducted in the form of a survey addressed to ninth-graders (N=440) and parents and carers (N=289) in Finnish Lapland in 2018. Both quantitative and qualitative analyses were performed on the data. The results show that most students from families with unsupportive family atmosphere and parenting did not wish to seek help. Still, among the whole study population, most of the young people experienced school as a natural place to receive extensive support for well-being. Both students and parents and carers wanted school to be a low-threshold place with various professionals who see, hear and support the students as needed. However, the challenge is to develop services that help struggling families. It would be necessary to invest in the development of collaborative, multi-agent school cultures that nurture students' initiative and engagement. We call this approach sustainable well-being which means working continuously to build trust and support for young people every day.